Rancang Bangun Game 3D Edukasi Basic Web Development Menggunakan Unity 3D - Rendy Irawan; Yunita Sari Siregar; Mufida Khairani (Jurnal Komputer Teknologi Informasi Sistem Komputer (JUKTISI), 2024)
The development of games is a media that is favored by the public which can have good or bad effects, where a game is basically made as for entertainment but there are also those who use games as educational media. This research was conducted to create a basic web development educational game packaged in the form of RPG (Role Playing Games) games with the result that providing basic web development education that can be played by all audience, where learning about web development is currently quite popular with some people. The game system design process is made using UML diagrams which will be applied to the unity 3D application and the assessment obtained through a questionnaire of 82% of respondents agreed that this game can be provide basic web development education. This game is also implemented using a finite state machine algorithm that controls enemy behavior in each state and collision detection for interaction with other objects. In this process create several interface designs and also for the finite state machine algorithm implemented to the enemy animator to control the state of enemy behavior, and the collision detection algorithm is applied to areas that have a collider to display the interface and also play background music.